Effects of the signal modulation on the response of human fibroblasts to in vitro stimulation with subthermal RF currents. (2nd January 2021) - Trillo, María Ángeles; Martínez, María Antonia; Úbeda, Alejandro
ABSTRACT: Capacitive-Resistive Electric Transfer (CRET) thermotherapies aim at tissue repair and regeneration through non-invasive application of RF currents. We have reported that the cellular response to subthermal CRET currents is non-linearly dependent on the signal frequency, and that in vitro exposure to a 448-kHz CRET signal promotes ADSC proliferation, as well as collagen and glycosaminoglycan synthesis in prechondrocytic cells. The present work investigates the response of neonatal fibroblasts to subthermal exposure (100 µA/mm 2 ) to two CRET signals: a 448-kHz, non-modulated sinusoidal wave vs. a 20-kHz amplitude-modulation of the 448-kHz carrier. To that end, cell proliferation and expression of the biomarkers Hsp47, Hsp27 and decorin were assessed by cell count, PCNA and Western blotting. The results revealed that while both signals significantly and equivalently increased early (4 h) expression of Hsp47, the modulated signal was more efficient in inducing Hsp27 and decorin overexpression and promoting cell proliferation. These data indicate that the cellular response is dependent on the RF signal modulation and suggest that the therapeutic effects of CRET could be mediated by promotion of fibroblastic proliferation and overexpression of biomarkers that are essential in skin regeneration.